Sifat Organoleptik dan Nilai Gizi MP-ASI dari Imbangan Ubi Jalar dan Kacang Hijau - Hendrawan, Hendrawan (Ma'soem University, 2025)
Infant until 6 months are generally given only breast milk. When the age more than 6 months, infant needs more vitamins, mineral, protein and carbohydrates that cannot be fulfilled from breast milk. Therefore, since the age of 6 months, infant need breastfeeding complementary food (MP-ASI) to meet their nutrition need. MP-ASI can be made by combining local raw material with milk powder. Research had been conducted to combine milk powder, red sweet potato flour and mung beans flour. The objective of the research was to determine the right balance of milk powder, red sweet potato flour and mung beans flour to produce MP-ASI with good organoleptic characteristics and nutrition content. The experimental method was applied in this research through Randomized Block Design with 7 treatments and each one repeated 4 timed. The treatments were the balance of milk powder, red sweet potato flour and mung beans flour those were A=50: 35: 15, B=50: 30: 20, C=50: 25: 25, D=50: 20: 30, E=50: 15: 35, F=50: 10: 40, and G=50: 5: 45. The results were analyzed statistically with variant analysis, and continued with Duncan Multirange Test. Result of the research indicated that the balance of 50: 5: 45 produced the finest MP-ASI according to organoleptic characteristics taste, color, aroma and texture. This balance produced energy 364ccal and 27,87 grams of protein.